Factors Related to Phlebitis in Internal, Surgical and Child Hospital Treatment Rooms - Setyaningsih, Rahayu; Rasmita, Dina; Jaya, Rachmad; Rosida, Rosida; Ervan, Ervan; Rahakbauw, Grenny Zovianny; Febrianti, Nur (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Phlebitis is an inflammation of the veins that occurs as a result of unsuccessful vein puncture, contamination of IV equipment and inadequate use of hypertonic solutions which can chemically irritate the veins. To minimize the risk of infection, nurses need to be aware of and recognize which factors are dominant in the incidence of phlebitis. This study aims to determine the incidence of phlebitis in the internal, surgical and pediatric ward of the hospital. The research design used was an analytic survey with a prospective (Study Cohort) approach, which is an observational study, meaning that the risk factors to be studied are identified first. It is then followed up prospectively. Sampling was carried out by purposive sampling method with a total sample of 57 people, then the results were tested using a computer program with the Chi Square test with a significance level of α = 0.05. The results of this study showed that there was no relationship between age and the incidence of phlebitis (p value = 0.531 > 0.05), there was a relationship between gender and the incidence of phlebitis (p value = 0.007 <0.005), there was a relationship between the size of intravenous catheter cannula and the incidence of phlebitis (p value = 0.001 < 0.05), there was no relationship between the type of fluid and the incidence of phlebitis (p value 0.373 > 0.05), there was a relationship between the type of infusion set and the incidence of phlebitis (p value 0.016 < 0.05), and There is a relationship between the infusion procedure and the incidence of phlebitis (p value 0.004 <0.05). The conclusion is that there is a relationship between gender, type of infusion set, size of intravenous catheter cannula, infusion procedure and no relationship between age and type of fluid with the incidence of phlebitis.